Impact of Xylitol Replacement on Physicochemical, Sensory and Microbial Quality of Cookies - Mushtaq, Zarina; Salim-ur-Rehman; Zahoor, Tahir; Jamil, Amir (Pakistan Journal of Nutrition, 2010)
Effect of replacement of xylitol on physicochemical, sensory and microbiological parameters of cookies were studied. Sucrose was replaced with xylitol at various levels ranging from 25-100%. Physico-chemical, microbiological and sensory evaluation of cookies at different intervals of storage i.e. 0, 15, 30, 45 and 60 days was carried out to find out the best treatment for commercialization. The results pertaining to sensory evaluation of cookies indicated that T2 (50% sucrose + 50% xylitol) got the highest score for fresh cookies which subsequently decreased but remained the highest during storage after 60 days. There was a significant change in moisture content while non-significant changes were recorded in fat, ash, protein, fiber and NFE contents. In cookies increasing trend in moisture content and decreasing trend in other parameters with storage was observed. Physical analysis revealed that hardness was observed the highest in cookies containing 100% sucrose which decreased significantly with increase in replacement of sucrose with xylitol. Fructurability values increased from cookies containing 100% sucrose to cookies containing 100% xylitol showing that cookies with sucrose were more crunchy. Color and water activity of cookies increased significantly in cookies containing 100% sucrose. It decreased with an increase of xylitol in cookies. Microbiological load was also maximum in cookies having 100% sucrose as compared to cookies containing 100% xylitol.